The role of regulatory fit on the attraction effect - Chatterjee, S.; Roy, Rajat; Malshe, A. (Elsevier Inc., 2011)
We show that adding entrant brands to a choice set compr ising of a predominantly promotion brand and a predominantly prevention brand can make both promotion and prevention-oriented consumers susceptible to the attraction effect. If an entrant targets the brand possessing superior promotion (prevention) feature, the resulting dominance relationship allows the promotion (prevention) focused consumers to sustain their regulatory focus. Entrant brands (and the associated dominance heuristic) therefore contribute to decision value by allowing both promotion and prevention-focused consumers pursue their goal in a way that fits with their regulatory concerns.